Analyzing the percentage of different PD‐1+ T cell subsets in peripheral blood and bronchoalveolar lavage fluid of small cell lung cancer patients: A prospective study. (30th August 2019) - Hu, Xintong; Gu, Yue; Li, Dan; Zhao, Songchen; Hua, Shucheng; Jiang, Yanfang
Abstract: The present study was designed to evaluate the percentage of different programmed cell death‐1 (PD‐1) + T cell subsets in peripheral blood and bronchoalveolar lavage fluid (BALF) of small cell lung cancer (SCLC) patients. The percentages of PD‐1 + T cell subsets in peripheral blood and BALF samples obtained from 52 lung cancer and 20 pneumonia patients, and 20 healthy controls were examined by flow cytometry. In addition, clinical parameters, such as erythrocyte sedimentation rate (ESR) and C‐reactive protein (CRP) levels, were also determined using Spearman's correlation test to assess their association with PD‐1 + T cell subsets. These present results revealed that the percentage of circulating PD‐1 + Tfh and peripheral helper T cells (Tph) cells significantly increased in peripheral blood of SCLC patients, when compared to non‐small cell lung cancer (NSCLC) pneumonia patients and healthy controls. In addition, PD‐1 + Tfh cells were also significantly enhanced in patients in the extensive‐stage group. In contrast, the BALF samples of SCLC patients exhibited a significant decrease in percentage of Tph cells. An overall imbalance was observed between PD‐1 + Tfh and Tph cells in both compartments. Furthermore, SCLC patients exhibited a significant decrease in the percentage of circulating PD‐1 + Tfh and Tph cells following chemotherapy, and the in vitro analysis revealed that the concentration of IL‐2 and IFN‐γ derived from PD‐1 + Tfh cells in SCLC were significantly lower than that from NSCLC. However, this had no significant correlation with disease severity. The present study indicated that elevated circulating PD‐1 + T cells can primarily be used as a biomarker for disease diagnosis and a potential therapeutic target.